Physarum panchganensis: A New Species of Myxomycetes from Panchgani (International Journal of Food and Nutritional Sciences, 2021)
The present study is the floristic study of one new species of Physarum pachganensis Nanir et al.,sp. nov. Near about thousands of specimens are described throughout the western part of Maharashtrawhich grow in natural habitat. Newly recorded specimen was described from the natural habitat grown onangiospermic plant leaves which is the first report from Panchgani, Maharashtra (India).